Emotional Impact of In Vitro Fertilization (IVF): Anxiety, Depression, and Their Relationship with Pregnancy Outcomes - Agiananda, Feranindhya; Natadisastra, Raden Muharram; Amir, Nurmiati; Irwanto; Aninditha, Tiara; Wibisono, Sasanto; Wahmurti, Tuti; Kekalih, Aria; Karnasih, Artasya; Samjunanto, Achmad; Puspaseruni, Putri Air; Velyani, Dyani Pitra; Prayangga, Regina (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objectives: Infertility can significantly impact women's physical and psychological health. Numerous treatment options are commonly pursued, with IVF often considered the last resort for infertile couples. However, IVF is associated with increased stress at every stage, potentially influencing women's perceptions and experiences throughout the procedure. This research examines anxiety and depression faced by women at different stages of IVF and analyzes their association with pregnancy outcomes. Methods: This cohort study was conducted at Dr. Cipto Mangunkusumo General Hospital and Dr. Sander B. Daya Medika Clinic from May 2018 to March 2023. Data were collected using questionnaires and assessments during IVF, focusing on the evaluation of anxiety, depression, and pregnancy outcomes. Chi-square and Fisher’s exact test was used to assess associations between variables, while Friedman ANOVA was used for longitudinal analysis of anxiety and depression scores during IVF. Results: The final analysis comprised 61 participants. The study revealed significant changes in anxiety and depression throughout IVF. Both anxiety (p < 0.001, Kendall’s w = 0.19) and depression levels (p = 0.001, Kendall’s w = 0.121) showed a significant rise across the IVF timeline. There is no statistically significant association between anxiety and depression scores and pregnancy outcomes across three measurement points during IVF (p > 0.05). Conclusion: Anxiety and depression significantly increase during IVF but do not affect clinical pregnancy rates. These findings highlight the importance of mental health screening and psychiatric support during IVF to ensure women’s comfort and enable them to navigate IVF more effectively. Keywords: Anxiety, Depression, Pregnancy Outcomes, Women, In Vitro Fertilization (IVF)